The Role of the Deep Learning Approach in Developing Digital Literacy and Character in Elementary Schools - Nugraha, Muhamad Ikhwan; Heryani, Rina; Riyana, Cepi (International Conference on Elementary Education, 2025)
Elementary school students are among the largest users of digital devices who are vulnerable to digital crime threats. The use of digital platforms by elementary school students must be accompanied by the developmentof digital literacy skills and the instillation of strong character, so that they do not become victims or perpetrators of digital violations. This research aims to examine the role of the deep learning approach in developing digital literacy and character skills in elementary schools. This study uses qualitative research with observation, interview, and questionnaire techniques involving 30 phase C students and teachers at one of the public elementary schools in Lembang District, West Bandung Regency. The findings in this study indicate that the teacher has implemented deep learning principles that emphasize students' learning experiences as mindful, meaningful, and joyful. The deep learning approach can indirectly encourage students to independently acquire information and develop their digital literacy skills. Deep learning education can also encourage students to develop various knowledge they acquire into a way of life. The deep learning approach plays an important role in creating learning situations that can develop students' digital literacy and character.